You are on page 1of 24
  • 3.3 PROPERTIES OF LOGARITHMS

  • 3.4 EXPONENTIAL AND LOGARITHMIC EQUATIONS

Copyright © Cengage Learning. All rights reserved.

What You Should Learn

Use the change-of-base formula to rewrite and evaluate logarithmic expressions.

Use properties of logarithms to evaluate or rewrite logarithmic expressions.

Use properties of logarithms to expand or condense logarithmic expressions.

Use logarithmic functions to model and solve real-life problems.

What You Should Learn

Solve simple exponential and logarithmic equations.

Solve more complicated exponential equations.

Solve more complicated logarithmic equations.

Use exponential and logarithmic equations to model and solve real-life problems.

Change of Base

Change of Base

Change of Base 5

Example 1 Changing Bases Using Common Logarithms

a.

Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6
Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6
Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6

b.

Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6
Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6
Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6
Example 1 – Changing Bases Using Common Logarithms a. b. Use a calculator. Simplify. 6

Use a calculator.

Simplify.

Properties of Logarithms

Properties of Logarithms

Properties of Logarithms 8

Example 3 Using Properties of Logarithms

Write each logarithm in terms of ln 2 and ln 3.

a. ln 6

b. ln

Example 3 – Using Properties of Logarithms Write each logarithm in terms of ln 2 and

Solution:

a. ln 6 = ln (2 3) = ln 2 + ln 3

b. ln

Example 3 – Using Properties of Logarithms Write each logarithm in terms of ln 2 and

= ln 2 ln 27 = ln 2 ln 3 3 = ln 2 3 ln 3

Rewrite 6 as 2 3. Product Property

Quotient Property Rewrite 27 as 3 3 . Power Property

Rewriting Logarithmic Expressions

Example 5 Expanding Logarithmic Expressions

Expand each logarithmic expression.

a.

log 4 5x 3 y

b.

b.

Solution:

a.

log 4 5x 3 y = log 4 5 + log 4 x 3 + log 4 y

= log 4 5 + 3 log 4 x + log 4 y

Product Property Power Property

Example 5 Solution

b.

Example 5 – Solution b. cont’d Rewrite using rational exponent. Quotient Property Power Property 12
Example 5 – Solution b. cont’d Rewrite using rational exponent. Quotient Property Power Property 12

cont’d

Rewrite using rational exponent.

Quotient Property

Example 5 – Solution b. cont’d Rewrite using rational exponent. Quotient Property Power Property 12

Power Property

Introduction

Introduction

One-to-One Properties

a x = a y if and only if x = y. log a x = log a y if and only if x = y.

Inverse Properties

a log a x = x

log a a x = x

Example 1 Solving Simple Equations

Original

Equation

  • a. 2 x = 32

  • b. ln x ln 3 = 0

Example 1 – Solving Simple Equations Original Equation a. 2 = 32 b. ln x –
  • c. = 9

  • d. e x = 7

  • e. ln x = 3

  • f. log x = 1

  • g. log 3 x = 4

Rewritten

Equation

Solution

Property

2 x = 2 5

x = 5

One-to-One

ln x = ln 3

x = 3

One-to-One

3 x = 3 2

x = 2

One-to-One

ln e x = ln 7

x = ln 7

Inverse

e ln x = e 3

x = e 3

Inverse

10 log x = 10 1

x = 10 1 =

10 = 10 x = 10 = Inverse

Inverse

3 log 3 x = 3 4

x = 81

Inverse

Introduction

Introduction 16

Solving Exponential Equations

Example 2 Solving Exponential Equations

Solve each equation and approximate the result to three

decimal places, if necessary.

a. e x 2 = e 3x 4

b. 3(2 x ) = 42

Example 2(a) Solution

e x 2 =

e 3x 4

x 2 = 3x 4

  • x 2 3x 4 = 0

Write original equation.

One-to-One Property

Write in general form.

(x + 1)(x 4) = 0

Factor.

(x + 1) = 0

  • = 1

    • x Set 1st factor equal to 0.

(x 4) = 0

  • = 4

    • x Set 2nd factor equal to 0.

The solutions are x = 1 and x = 4. Check these in the

original equation.

Example 2(b) Solution

cont’d

3(2 x ) = 42

2 x = 14

log 2 2 x = log 2 14

  • x = log 2 14

x =  3.807
x
=
 3.807

Write original equation.

Divide each side by 3.

Take log (base 2) of each side.

Inverse Property

Change-of-base formula

The solution is x = log 2 14 3.807. Check this in the

original equation.

Solving Logarithmic Equations

Solving Logarithmic Equations

To solve a logarithmic equation, you can write it in

exponential form.

ln x = 3

e ln x = e 3

x = e 3

Logarithmic form

Exponentiate each side. Exponential form

This procedure is called exponentiating each side of an

equation.

Example 6 Solving Logarithmic Equations

a. ln x = 2

e ln x = e 2

x = e 2

b. log 3 (5x 1) = log 3 (x + 7)

5x 1 = x + 7

Original equation

Exponentiate each side.

Inverse Property

Original equation

One-to-One Property

4x = 8

Add x and 1 to each side.

x = 2

Divide each side by 4.

Example 6 Solving Logarithmic Equations

cont’d

c. log 6 (3x + 14) log 6 5 = log 6 2x

Example 6 – Solving Logarithmic Equations cont’d c. log (3 x + 14) – log 5
Example 6 – Solving Logarithmic Equations cont’d c. log (3 x + 14) – log 5

3x + 14 = 10x

7x = 14

x = 2

Original equation

Quotient Property of Logarithms

One-to-One Property

Cross multiply.

Isolate x.

Divide each side by 7.